BLADDER INFLATION PRIOR TO CESAREAN SECTION CAN PREVENT BLADDER INJURY IN HIGH RISK PATIENTS - NASEEB , S; MURAD , S; RASHID , S; NADEEM , S; NADEEM , A; KHATOON , A (Biological and Clinical Sciences Research Journal, 2023)
This study aimed to evaluate the effectiveness of inflating the urinary bladder immediately before cesarean section (CS) in reducing the chances of bladder injury in high-risk patients. This was a prospective randomized controlled trial. The study was conducted in Obstetrics and Gynecology Ward 8, Jinnah Postgraduate Medical Centre (JPMC) Karachi, from April 06, 2021 to September 30, 2021. Three hundred twenty-eight pregnant women who delivered by cesarean section and had one or more risk factors for urinary tract injury were recruited. The women were divided into two groups: Group A underwent bladder inflation using a triple-way Foley catheter before CS, while Group B served as the control group without bladder inflation with a Foley catheter before CS. In this study, urinary bladder injury was found in 5.5% of women in Group A who had bladder inflation, while 12.2% of women in Group B without bladder inflation had bladder injury. The efficacy in Group A and B was 94.5% and 87.8%, respectively. The results showed a significant association between the study group and urinary bladder injury (p=0.032). The study significantly reduced urinary bladder injuries, surgery time, blood transfusion, and hospitalization. Inflating the urinary bladder before cesarean section should be used to prevent bladder injury in women with risk factors for dense bladder adhesion.